Geographical Indications under International Intellectual Property Law: An Indonesian Perspective - Warokka, Mariana Molnar Gabor (UI Scholars Hub, 2011)
There are currently two systems for the registration of GI and Appellations of Origin. First, the Lisbon Agreement for the Protection of Appellations of Origin and their International Registration of 1958. Second, the Madrid Agreement Concerning the International Registration of Marks and the Madrid Protocol of 1989 for countries that protect GI under the trade mark regime. Indonesia has provided for GI protection under its Trade Mark Law No. 15 of 2001, and the appertaining Government Regulation No. 51 of 2007 concerning Geographical Indication. Several cases have been reported of Indonesian GI potential products, such as Kopi Toraja and Kopi Gayo, being registered overseas as trade mark by foreign companies. Consequently, local farmers are prevented from exporting their traditional products using their own local name. In the context of international economic law, this paper is aimed at discussing three related issues, namely, what are the remedies available to Indonesia under international law to protect its GI products from misappropriation; second, to what extent can these legal remedies be expected to be effective in resolving the issue; and third, to what extent would signing the Lisbon and/or Madrid Agreement benefit Indonesia in the form of greater international protection of its GI products?